Jak urzeczywistniać ideę samorządności terytorialnej w państwie unitarnym? Przykład centrów usług społecznych - Rymsza, Marek (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2021)
A specific quality of Poland with its administrative framework is a successful combination of the unitary character of the state and well-developed structures of the local government. Institutional solutions underlying this effective merger were adopted at the early stages of a new, independent Polish state in 1918, and then renewed through the process of political transformation from communism to democracy dating back to 1989. The self-governance was also one of the main values promoted by the Solidarity Movement. A specific sphere of public administration where territorial self-governance may find its successful practical implementation within the unitary state are social services, which constitute one of the three systemic pillars of the developed European welfare states. Since 1990, social welfare in Poland is administered at the level of state social policy, whose specific functions are realized through local government infrastructure. Social Service Centres constitute a new instrument for the development of local social services, acting pursuant to the 2019 Act on Social Services Delivered by the Social Service Centre. The self-governance of local communities is facilitated there through the package of directional principles how to deliver social services, which rely on the subsidiarity of the state, sustainability of social bonds, co-operation between public administration and civil sector entities and universal access of citizens to social services.